Global quality status in Mediterranean aquaculture - Hough C. (Global quality assessment in Mediterranean aquaculture, 2000)
For many consumers, there are good (high quality) and poor (low quality) species where the initial determination of quality may be based on such criteria as: (i) visual perception; (ii) taste; and (iii) trust (that the supplier is providing a good product). The translation of these different perceptions of quality into the aquaculture chain remains an extremely complicated and ever-changing process. While some Mediterranean countries belong to the European Union and have common legislation that affects 'quality', others have significant production for local and non-EU Mediterranean markets and, therefore, the overall concepts applied to 'quality' can change. The establishment of procedures and standards is essential for the successful incorporation of quality into any process. Some aquaculture companies (usually those who are vertically integrated and market the final product) are submitting for ISO (International Standards Organisation) approval.
Workshop of the CIHEAM Networks on Technology of Aquaculture in the Mediterranean (TECAM) and Socio-Economic and Legal aspects of Aquaculture in the Mediterranean, 1999/11/29-1999/12/01, Barcelona (Spain)